The significance of blood pressure variation and metabolic risk factors in patients with different stages of hypertension - Sun Min Kim; In Kyoung Shim; Ju Won Lee; Jun Yeob Lee; Si Won Lee; Kyoung Im Cho; Hyun Su Kim; Jae Woo Lee; Jung Ho Heo (Kosin Medical Journal, 2017)
Objectives Blood pressure variation (BPV) and metabolic syndrome is an independent risk factor for cardiovascular events. Ambulatory blood Pressure (ABP) has been shown to be more closely related to cardiovascular events in hypertensive patients than conventional office BP (OBP). Using both OBP and ABP, 4 groups of patients were identified: (1) normotensive patients (NT); (2) white coat hypertensives (WCHT); (3) masked hypertensives (MHT); and (4) sustainedhypertensives (SHT). We investigated the significance of BPV and metabolic risks of these 4 groups. Methods This study is a retrospective analysis of patients between January 2008 and May 2013. Echocardiography and 24 hour ABP monitoring were performed. Results BMI was significantly higher in the MHT compared with the NT. There were progressive increases in fasting glucose level from NT to WCHT, MHT, and SHT.MHT and SHT had higher 24h and nighttime BPV than NT.MHT was significantly related with BMI (r = 0.139, P = 0.010), creatinine (r = 0.144, P = 0.018), fasting glucose (r = 0.128, P = 0.046), daytime systolic BPV (r = 0.130, P = 0.017), and daytime diastolic BPV (r = 0.130, P = 0.017). Dyslipidemia (r = 0.110, P = 0.043), nighttime systolic BPV (r = 0.241, P < 0.001) and nighttime diastolic BPV (r = 0.143, P = 0.009) shown correlation with SHT. In multivariate logistic regression, MHT was independently associated with Body mass index (OR 1.086, 95% CI 1.005–1.174, P = 0.038) and creatinine (OR 1.005, 95% CI 1.001–1.010, P = 0.045). Conclusions BPV and metabolic risk factors were found to be greater in MHT and SHT compared with NT and WCHT. This suggests that BPV and metabolic risks may contribute to the elevated cardiovascular risk observed in patients with MHT and SHT.